2016
DOI: 10.1186/s13643-016-0380-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the validity of abbreviated literature searches for rapid reviews: protocol of a non-inferiority and meta-epidemiologic study

Abstract: BackgroundSystematic reviews offer the most reliable and valid support for health policy decision-making, patient information, and guideline development. However, they are labor intensive and frequently take longer than 1 year to complete. Consequently, they often do not meet the needs of those who need to make decisions quickly. Rapid reviews have therefore become a pragmatic alternative to systematic reviews. They are knowledge syntheses that abbreviate certain methodological aspects of systematic reviews to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Literature searching for qualitative studies, and in public health topics, typically generates a greater number of studies to sift than in reviews of effectiveness [ 39 ] and demonstrating the ‘value’ of studies identified or missed is harder [ 56 ], since the study data do not typically support meta-analysis. Nussbaumer-Streit et al (2016) have registered a review protocol to assess whether abbreviated literature searches (as opposed to comprehensive literature searches) has an impact on conclusions across multiple bodies of evidence, not only on effect estimates [ 57 ] which may develop this understanding. It may be that decision makers and users of systematic reviews are willing to trade the certainty from a comprehensive literature search and systematic review in exchange for different approaches to evidence synthesis [ 58 ], and that comprehensive literature searches are not necessarily a marker of literature search quality, as previously thought [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Literature searching for qualitative studies, and in public health topics, typically generates a greater number of studies to sift than in reviews of effectiveness [ 39 ] and demonstrating the ‘value’ of studies identified or missed is harder [ 56 ], since the study data do not typically support meta-analysis. Nussbaumer-Streit et al (2016) have registered a review protocol to assess whether abbreviated literature searches (as opposed to comprehensive literature searches) has an impact on conclusions across multiple bodies of evidence, not only on effect estimates [ 57 ] which may develop this understanding. It may be that decision makers and users of systematic reviews are willing to trade the certainty from a comprehensive literature search and systematic review in exchange for different approaches to evidence synthesis [ 58 ], and that comprehensive literature searches are not necessarily a marker of literature search quality, as previously thought [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The primary outcome of this study was the proportion of concordant conclusions between the rapid reviews and the Cochrane reviews. To address this outcome, we applied a method by Nussbaumer-Streit et al [23]. We considered studies as identified if at least one publication of a relevant study had been included.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of studies that were missed on effect estimates of meta-analyses, however, was small [ 24 ]. An ongoing methods project uses a non-inferiority and meta-epidemiological approach to assess whether the reduced sensitivity of abbreviated searches has an impact on conclusions of Cochrane reviews, not only on effect estimates [ 25 ].…”
Section: Discussionmentioning
confidence: 99%